2012
DOI: 10.1007/s00264-011-1463-8
|View full text |Cite
|
Sign up to set email alerts
|

Patellar resurfacing as a second stage procedure for persistent anterior knee pain after primary total knee arthroplasty

Abstract: Purpose Knee pain after total knee arthroplasty may be caused by an unresurfaced patella. Secondary isolated resurfacing of the previously unresurfaced patella in total knee arthroplasty remains controversial. The aim of this retrospective study was to evaluate the outcome after patellar resurfacing as a second stage procedure. Methods The study included 22 patients (13 female/nine male) who underwent resurfacing of the patella with a mean follow-up of 61.8±39.2 months. The mean age of the patients was 60±9.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…Additionally, our results confirm that secondary patellar resurfacing for anterior knee pain in the setting of a previously not resurfaced patella does not necessarily result in the resolution of the pain [30][31][32][33][34][35][36][37][38]. As noted by Burnett [39] there are many causes of anterior knee pain other than the patellofemoral joint.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, our results confirm that secondary patellar resurfacing for anterior knee pain in the setting of a previously not resurfaced patella does not necessarily result in the resolution of the pain [30][31][32][33][34][35][36][37][38]. As noted by Burnett [39] there are many causes of anterior knee pain other than the patellofemoral joint.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study revealed improvements in knee scores in a similar percentage of cases, with a specific cause for anterior knee pain being unknown [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Search strategy and results are summarized in the Figure. A total of 52 titles were reviewed, of which 16 studies underwent a full-text review, of which 15 studies fulfilled the inclusion criteria and were included in the current review. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Summary data and quality of the included studies according to GRADE are reported in Table 1. Of the 15 included studies, 2 randomized, controlled trials (RCTs) were identified, 18,21 although the outcomes of secondary patellar resurfacing were not the focus of these RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 15 included studies specifically stated the number of patients satisfied with the procedure. [9][10][11][12]16,17,19,22,23 Patient satisfaction in these 9 studies varied 12/20 relief of pain.…”
Section: Patient Satisfactionmentioning
confidence: 99%